HUBUNGAN DUKUNGAN SOSIAL KELUARGA DENGAN KEPATUHAN MINUM OBAT PADA PASIEN ODGJ DI UPT PUSKESMAS KEDUNGJAJANG KABUPATEN LUMAJANG - Purwono, Siswo; Hamim, Nur; Abidin, Zainal (NHM PRESS, 2024)
Patients with mental disorders, are those who experience disturbances in their thoughts, feelings and behavior. Families with individuals who experience mental disorders will provide a negative social model. Families who can’t handle it, may deal with many challenges, including difficulties in the healing process, for family members who suffer from mental illness and lack of supervision in taking medication. The aim of this research is to determine the correlation between family social support and medication adherence in PWMD patients at the Kedungjajang Community Health Center, Lumajang Regency. This research design uses a cross sectional design. Sampling used an accidental sampling technique with a sample size of 56 respondents carried out from 1 to 31 July 2024. The instrument used for data collection was a questionnaire. The results of the study showed that of the 56 respondents' social support for adherence to taking medication for PWMD patients, 54 (96.4%) were good, while 51 (91.1%) of ODGJ patients were compliant in taking medication for PWMD. Data processing using the chi square test calculated using SPSS Windows obtained a value of p=0.038 (p<0.05) so it can be concluded that Ha is accepted, meaning there is a significant correlation between family social support and adherence to taking medication in PWMD patients at the Kedungjajang Community Health Center, Lumajang Regency. in 2024. As a nurse we are expected to improve communication, information, and education to the family of PWMD. It can help families play a bigger role in providing the best social support to PWMD patients and monitor medication adherence in PWMD patients.